Thinking Through the History of the Book - Howsam, Leslie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2016)
An impressive body of meticulous scholarship in the history of the book has led scholars to reject outmoded models of revolutionary change and technological determinism, and instead to explore themes of evolution and organic change. Similarly, the old unitary and Eurocentric book history is being supplanted by a series of parallel narratives where the focus is on human adaptation of new technologies to newly felt needs and fresh marketing opportunities. The article suggests that the study of book history is a way of thinking about how people have given material form to knowledge and stories. It highlights some particularly ambitious recent arguments, and emphasizes research, theory and pedagogy as the means to a wider understanding. Rather than being an academic discipline, book history is identified as an “interdiscipline,” an intellectual space where scholars practicing different disciplinary approaches and methodologies address the same capacious conceptual category.